State Responsibility for Environmental Pollution from a Human Rights Perspective - Firman Octhaviana Sulistiyono (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Environmental pollution due to suboptimal waste management is a problem that continues to increase along with increasing population growth, urbanization, and changes in people's consumption patterns. This condition not only has a negative impact on ecology, but also has an impact on health, quality of life, and provides human rights. This study aims to analyze the state's responsibility for environmental pollution due to waste and examine waste management from a human rights perspective. The research method used is normative juridical research with a regulatory approach (statutory approach) and a contextual approach (conceptual approach). The results of the study indicate that the state has constitutional and juridical responsibilities in ensuring effective waste management, as regulated in Law Number 18 of 2008 concerning Waste Management and Law Number 32 of 2009 concerning Environmental Protection and Management. From a human rights perspective, a good and healthy environment is a fundamental right guaranteed in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia and various international human rights instruments. Therefore, environmental pollution resulting from poor management can be considered a threat to the rights to health, the right to life, and the right to a decent environment. Sustainable waste management is a crucial instrument for realizing environmental protection and guaranteeing human rights.